2006
DOI: 10.1002/mop.21860
|View full text |Cite
|
Sign up to set email alerts
|

Novel filter using composite right/left-handed transmission line

Abstract: A novel filter using composite right/left‐handed (CRLH) transmission line (TL) unit cells is designed, fabricated, and measured. After properly designing the parameters of the capacitors and the inductors, we have generated a narrow bandpass filter. The simulation results show that the bandpass filter with 4 CRLH TL unit cells has very small loss in the passband and very sharp transitions at the edges of the passband. The performances of the proposed filter are demonstrated by measured results, which are in go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The concept of composite right/left-handed (CRLH) trmission line, introduced by Caloz et al In [4], shown great potential in engineering applications [5]. One of the most interesting field is the filter applications [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of composite right/left-handed (CRLH) trmission line, introduced by Caloz et al In [4], shown great potential in engineering applications [5]. One of the most interesting field is the filter applications [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In other ways, because the first experimental demonstration of a double negative medium by Smith et al in 2000 [7] and the concept of composite right/left-handed (CRLH) transmission line was introduced by Caloz et al in 2003 [8,9], a large number of filters design using these theory have already been demonstrated [10][11][12][13][14][15]. Complementary split-rings resonators and series gaps were both used in [10,11], and grounded stubs and open stubs were also blended in [10,11], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Complementary split-rings resonators and series gaps were both used in [10,11], and grounded stubs and open stubs were also blended in [10,11], respectively. Interdigital coupled lines and grounded stubs were used as series capacitors and shunt inductors in [12], whereas lumped elements were used in [13] to construct CRLH transmission for BPF application. In [14], two linear arrays of metallic vias and short-stubs inductors were used to generate shunt inductors besides the series interdigital capacitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods and structures have been used to achieve wide bandpass filters [1][2][3][4][5][6]. In addition, novel small size and low insertion loss bandpass filters are also required in wireless communication technology such as the Digital Communication System (DCS, 1710MHz~1880MHz) [7].…”
Section: Introductionmentioning
confidence: 99%